The ethical organization. - Costlow, T. (IEEE spectrum)
From the front-page scandals at WorldCom and Tyco to quieter issues like the theft of office equipment, there was usually a point when an employee knew what was happening and could have told someone to prevent further wrongdoing. At a growing number of companies, the question of whom to tell has a simple answer-the ethics officer. It's the ethics officer's role to help promote the company's values, making him- or herself available when employees feel those values are being compromised. In essence, they're a living reminder to employees that honesty and integrity matter.